CONSERVATION OF THE PACIFIC RIDLEY SEA TURTLE (LEPIDOCHELYS OLIVACEA, ESCHSCHOLTZ, 1829) AND TOURISM IN URBAN BEACHES: THE MAZATLAN AQUARIUM ON THE COAST OF THE MEXICAN PACIFIC - Grano-Maldonado, Mayra I. (2022)
This study shows the results of an interdisciplinary investigation on the conservation of the Olive Ridley sea turtle (Lepidochelys olivacea Eschscholtz, 1829), a species that is considered endangered according to the Mexican Standard (NOM-059-SEMARNAT-2010). This study shows the way in which some national institutions interact with tourist activity on urban beaches on the Mexican Pacific coast, particularly the Mazatlan Aquarium in Sinaloa. This aquarium is a para-statal entity governed by the city council of the city-port of Mazatlan, whose protection program for the Olive Ridley turtle is nationally recognized. For this study, interdisciplinary theoretical and methodological perspectives were built between fields of marine biology and comprehensive social sciences. The results show that, during two decades, 11,359 nests have been protected; 1,059,658 eggs recovered; 869,854 turtles released and a survival rate of 81.68%, all of this in a space where different interests converge, such as urban beaches which allow, through environmental education, the establishment of a mentality of care and connection with nature (sustainable) in the new generations of local citizens and tourists who visit the destination, discouraging the economic exploitation of the species in favor of the capitalist tourist company.